Correlation of Interleukin-17-Producing Effector Memory T Cells and CD4+CD25+Foxp3 Regulatory T Cells with the Phosphate Levels in Chronic Hemodialysis Patients - Cheng-Lin Lang; Min-Hui Wang; Kuan-Yu Hung; Sung-Hao Hsu; Chih-Kang Chiang; Kuo-Cheng Lu (The Scientific World Journal)
Background and Objectives. Hyperparathyroidism and hyperphosphatemia contribute to the inflammatory effects in chronic hemodialysis (HD) patients. Interleukin-17-producing CD4+ effector memory T (Th17) cells and CD4+CD25+Foxp3 regulatory T (Treg) cells both play critical roles in immune activation and inflammation. We investigated the relationship between the Treg and Th17 cells and the phosphate level in chronic HD patients. Methods. 105 patients aged ≥35 years on chronic HD over 3 months were enrolled. The peripheral blood mononuclear cells were collected, cultured, and stimulated by phytohemagglutinin-L, phorbol myristate acetate, and ionomycin at different time points for T cell differentiation. Results. The T cell differentiation was as follows: Th17 cells (mean ± standard deviation (SD): 25.61% ± 10.2%) and Treg cells (8.45% ± 4.3%). The Th17 cell differentiation was positively correlated with the phosphate and albumin levels and negatively correlated with age. The Treg cell differentiation was negatively correlated with albumin level and age. In the nondiabetes group (n=53), the Th17 cell differentiation was predominantly correlated with the phosphate and iPTH (intact parathyroid hormone) levels as well as the dialysis vintage. Conclusion. Higher phosphate and iPTH levels and longer dialysis duration may increase Th17 cell differentiation, especially in the nondiabetic chronic HD patients.